PERFORMANCE EVALUATION OF WAVE ENERGY CONVERTER BASED ON SIMULATION RESULTS OF WAVE MODEL SWAN (SIMULATING WAVES NEARSHORE). STUDY CASE: SOUTHERN JAVA COAST â WEST NUSA TENGGARA - Lathifa Sakina, Sholihati
The high demand for energy has caused Indonesian government to make several policies related to energy supply in order to overcome the crisis, namely by targeting supply of renewable energy resources at least 23% of total energy production in 2025 and 31% in 2050. As a maritime country, Indonesia has a great potential of wave energy that can be utilized as a source of renewable energy. The study area is located along the coast of southern Java – West Nusa Tenggara, since the area has high wave energy potential, a supportive environment, and large socio-economic impact. By using 5 years wind data input during 2016 - 2020 from ECMWF ERA 5 reanalysis, wave data in the study area is generated by using a SWAN (Simulating Waves Nearshore) model simulation. Two types of wave energy converter (WEC) namely Oscillating Water Column (OWC), represented by OE Buoy, and heaving device, described by Pontoon Power Converter, were selected for the utilization of wave energy in 8 study locations. The performance evaluation of the two WECs will be reviewed through several parameters, including the power produced by one unit of equipment, capacity factor (CF), power generated by the wave farm, and levelized cost of energy (LCOE) for each type of WEC. The model results show that there is a seasonal effect on wave conditions and energy potential in the study area. Both of significant wave height and wave energy potential reach their maximum (minimum) magnitudes during east monsoon/JJA (west monsoon/DJF). The WEC performance evaluation shows that the OE Buoy produces higher power and CF than the Pontoon. In addition, seasonal variabilities also affect the performance of the two WECs, where OE Buoy (Pontoon) has a better performance during the east (west) monsoon. However, results of LCOE calculation show that Pontoon provides cheaper electricity rates than OE Buoy electricity rates, but still higher than PLN rates. Among the 8 locations, southern coast of Lebak is the location with the highest WEC evaluation parameters, while southern coast of Lombok and Sumbawa are the locations with the lowest evaluation parameters.